Mineralogy and forms of potassium in red yellow latosol of a guava (Psidium guajava) tree orchard - NATALE, WILLIAM; JUNIOR, J MARQUES; BOARETIO, A E; SIMOES, F L (The Indian Journal of Agricultural Sciences, 2014)
A trial was conducted during 1994-95 to study the effect of potassium fertilization on a guava (Psidium guajava L.) culture for 3 years. The control plots (wtihout K) showed fruit production and potassium exportation that did not agree with the levels obtained by chemical analysis of the soil. Physical, chemicalm, potassium, with emphasis on the fact that guava trees have a considerably widespread root system. The results obtained confirmed the presence of minerals in this soil that can supply potassium to the trees through wearhering, Feldspars were identified in the silt fraction and micas in the clay fraction by X-ray diffractometry. The determination of total potassium revealed that the silt fraction of the soil had the hargest absolute amounts of potassium followed by clay. However, in view of its greater content, clay was the fraction that contributed most to the total amounts of potassium detected.